Experimental and simulation-based understanding of morphology controlled barium titanate nanoparticles under co-adsorption of surfactants - Sun, Zhongyu; Zhang, Lei; Dang, Feng; Liu, Yao; Fei, Zhiying; Shao, Qian; Lin, Hong; Guo, Jiang; Xiang, Lichen; Yerra, Narendranath; Guo, Zhanhu (CrystEngComm, 2017)
Well dispersed single-crystalline BaTiO 3 nanoparticles with controlled morphologies were synthesized using a thermohydrolysis route. The nanoparticles were tuned from spherical to cubic upon changing the NaOH concentration under a critical molar ratio of oleic acid to hydrazine. Density functional theory (DFT) and molecular dynamics (MD) calculations indicated that hydrazine molecules adsorbed preferably on the Ti position of the Ti-O terminated surface; meanwhile, oleic acid molecules tended to adsorb on the Ba position of the Ba-O terminated surface. The added hydrazine changed the formation mechanism of BaTiO 3 nanoparticles from an in situ growth to a dissolution-precipitation growth. Excellent dispersibility in aqueous solution was achieved for the BaTiO 3 nanoparticles under the assistance of hydrazine. Meanwhile, a high-quality self-assembled film with a stable dielectric constant of 30 in the frequency range from 0 Hz to 1 MHz was prepared using the well dispersed BaTiO 3 nanoparticles, providing a novel low-temperature route for the fabrication of perovskite films. Selective adsorption of surfactants was theoretically predicted on crystal faces to prepare well-dispersed nanoparticles for the self-assembly of a high-quality stable dielectric constant film.